2003
DOI: 10.1097/00002030-200309050-00012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of indinavir–ritonavir-based regimens in HIV-1-infected patients with prior protease inhibitor failures

Abstract: These results suggest that IDV-RTV-based regimens may be able to overcome IDV resistance. This underscores the importance of drug adherence, potency, and exposure in determining virologic responses to antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We have also reported preliminary findings suggesting that resistance is uncommon in treated individuals with poor adherence, and we have hypothesized that poor adherence leads to insufficient drug pressure to select for resistant virus 36,41 . Other recent studies also suggest that low adherence levels may not lead to the development of drug resistance 42,43 . The current finding that resistance is less common in a population with marginal adherence is consistent with this hypothesis, and suggests that, unlike the case with tuberculosis, marginalized populations may not be at greater risk for HIV antiretroviral resistance due to poor adherence.…”
Section: Discussionmentioning
confidence: 98%
“…We have also reported preliminary findings suggesting that resistance is uncommon in treated individuals with poor adherence, and we have hypothesized that poor adherence leads to insufficient drug pressure to select for resistant virus 36,41 . Other recent studies also suggest that low adherence levels may not lead to the development of drug resistance 42,43 . The current finding that resistance is less common in a population with marginal adherence is consistent with this hypothesis, and suggests that, unlike the case with tuberculosis, marginalized populations may not be at greater risk for HIV antiretroviral resistance due to poor adherence.…”
Section: Discussionmentioning
confidence: 98%
“…In a study 30 of 20 treatment-experienced recipients of indinavir at 800 mg twice per day plus ritonavir at 100 or 200 mg twice per day, the L90M mutation was identified in nonresponders and partial respondents but not in responders, despite more consistent through levels, as compared with standard indinavir dosing. On the contrary, another study by Campo et al 31 suggested that short-term virological suppression (HIV RNA level, < 400 copies/mL) is possible for subjects with previous failure of PI-based treatment with phenotypic resistance to indinavir when treated with indinavir plus ritonavir at 800 mg and 200 mg twice per day. These results demonstrated how the same dose change can result in lower rates of resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Studies performed to date include small, nonrandomized patient cohorts and lack appropriate control for baseline drug resistance to reliably assess response. [10][11][12][13] In vitro susceptibility studies 14 predict that indinavir enhancement with ritonavir will produce concentrations that exceed inhibitory concentrations for resistant isolates; however, virologic benefit remains to be confirmed clinically.…”
Section: Clinical Trialsmentioning
confidence: 99%